Accelerated Vascular Aging in Chronic Kidney Disease: The Potential for Novel Therapies. Issue 8 (14th April 2023) - Hobson, S.; Arefin, S.; Witasp, A.; Hernandez, L.; Kublickiene, K.; Shiels, P.G.; Stenvinkel, P.
Abstract : The pathophysiology of vascular disease is linked to accelerated biological aging and a combination of genetic, lifestyle, biological, and environmental risk factors. Within the scenario of uncontrolled artery wall aging processes, CKD (chronic kidney disease) stands out as a valid model for detailed structural, functional, and molecular studies of this process. The cardiorenal syndrome relates to the detrimental bidirectional interplay between the kidney and the cardiovascular system. In addition to established risk factors, this group of patients is subjected to a plethora of other emerging vascular risk factors, such as inflammation, oxidative stress, mitochondrial dysfunction, vitamin K deficiency, cellular senescence, somatic mutations, epigenetic modifications, and increased apoptosis. A better understanding of the molecular mechanisms through which the uremic milieu triggers and maintains early vascular aging processes, has provided important new clues on inflammatory pathways and emerging risk factors alike, and to the altered behavior of cells in the arterial wall. Advances in the understanding of the biology of uremic early vascular aging opens avenues to novel pharmacological and nutritional therapeutic interventions. Such strategies hold promise to improve future prevention and treatment of early vascular aging not only in CKD but also in the elderly general population.